2023
DOI: 10.7903/cmr.21892
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Perceived Employability and Sabotage Behavior: Moderating Roles of Perceived Organizational Support and Procedural Justice

Henry Edosomwan,
Tochukwu Oguegbe,
Chiamaka Joe-Akunne

Abstract: Sabotage behavior is a significant challenge that can undermine an organization's performance and effectiveness. The mechanism connecting perceived employability to sabotage behavior is under-researched in organizational behavior literature. Based on mentioned above and drawing on the social exchange theory, this study examined the moderating roles of perceived organizational support (POS) and procedural justice (PJ) in the relationship between perceived employability and sabotage behavior among employees in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…For example, the study conducted by Afsar and Badir (2016) indicated that POS promoted organizational citizenship behavior, while an investigation by Kura et al (2016) on a sample of public sector workers found that POS is linked to constructive deviance, especially in the presence of high organizational trust. Studies have also shown that social exchange constructs such as perceived knowledge sharing and support were positively linked with constructive deviance but showed a negative relationship with destructive deviance (Edosomwan et al, 2023;Malik & Malik, 2021). These studies supported the research finding by indicating that the likelihood of employees engaging in constructive deviance and other risk-related discretion and beneficial behaviors is higher employees perceive that their organization has regard for their contributions and well-being.…”
Section: Discussionsupporting
confidence: 74%
“…For example, the study conducted by Afsar and Badir (2016) indicated that POS promoted organizational citizenship behavior, while an investigation by Kura et al (2016) on a sample of public sector workers found that POS is linked to constructive deviance, especially in the presence of high organizational trust. Studies have also shown that social exchange constructs such as perceived knowledge sharing and support were positively linked with constructive deviance but showed a negative relationship with destructive deviance (Edosomwan et al, 2023;Malik & Malik, 2021). These studies supported the research finding by indicating that the likelihood of employees engaging in constructive deviance and other risk-related discretion and beneficial behaviors is higher employees perceive that their organization has regard for their contributions and well-being.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, most of this research focuses on procedural justice and elements of the budgeting process (budget participation), to predict a sense of fairness and the creation of slack. Then the third study conducted by Edosomwan et al, (2023) discusses the positive relationship between perceived employability and sabotage behavior. Perceived Organizational Support (POS) and procedural justice moderate the relationship between perceived employability and sabotage behavior.…”
Section: Introductionmentioning
confidence: 99%